STUDI GEOKIMIA TANAH DAN HUBUNGANNYA DENGAN MINERALISASI LOGAM DAERAH KETUNGAU HULU, KABUPATEN SINTANG, PROVINSI KALIMANTAN BARAT: STUDY OF SOIL GEOCHEMISTRY AND IT’S RELATIONSHIP WITH THE PRESENCE OF METAL MINERALIZATION IN KETUNGAU HULU AREA, SINTANG REGENCY, WEST KALIMANTAN PROVINCE - Nicolaus Bagus Krismantoro; Nurcahyo Indro Basuki; Hartaja Hatta Wicaksono; John Mauritz (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2022)
Ketungau Hulu is a gold prospect plan area in Sintang-Silantek Block on the island of Kalimantan which is a collaboration program between Indonesia (Geological Agency) and Malaysia (Jabatan Mineral and Geoscience). Administratively, the research area is located in Sintang Regency, West Kalimantan with an area of 18 km2. This study aims to identify the geological conditions, structure, alteration, and mineralization of the study area as well as potential anomalies for metal elements (Au, Cu, Pb, Zn, and Mn) based on soil geochemistry data and its relationship with the presence of mineralization. The study was conducted using soil samples from 84 points in the ridge and spur areas. In addition to soil samples, 48 rock samples and one sample from pan concentrate were also obtained. Furthermore, all samples were analyzed for chemical, geochemistry, statistic, petrology, petrographic, and mineragraphy. The research area consists of Greywacke Sandstone Unit, Arenite Sandstone Unit, and Diorite Intrusion Unit. Geological structure that developed in the area has relatively NNW-SSE and NW-SE trends. The alteration zones present in the research area are argillic zone and propylitic zone. Mineralization is found in dogtooth, crustiform, colloform, and assicular textured quartz veins with relative orientation directions NW-SE and NNE-SSW that presence of ore minerals such as native Au, chalcopyrite, pyrite, sphalerite, covellite, and from base metal contents abundance in the rock samples. The results of soil sample analysis showed that the Au had an anomaly value of log 1.90 ppb, Pb of sqrt 7.44 ppm, Zn of log 1.92 ppm, Cu of log 1.69 ppm, and Mn of log 2.46 ppm. Base metal elements anomaly is controlled by lithology, structure, and topography. Analysis using Pearson's product on base metal elements states that there are two groups of elements i.e., Au and Pb-Zn-Cu-Mn. Based on the anomaly distribution of base metal elements in soil and the presence of mineralization, it can be interpreted that there are four prospect area i.e., KU-1, KU-2, BE-1, and BE-2 prospects.